Membangun Kehidupan Rohani yang Kokoh dalam Konteks Kemajemukan bagi Murid-murid di Sekolah Kristen di Tana Toraja - Nely; Tandy, Benhur (Misioner, 2024)
In the face of the dynamic modern era, where rapid changes and diverse values are evolving, the challenge of maintaining a Christian identity is becoming increasingly significant. The diversity of society is one of the main triggers of this challenge, especially in two prominent aspects: social diversity and cultural diversity. This study aims to explore effective strategies for building a strong spiritual life in Christian schools, especially in the context of the diversity of Toraja society. By using descriptive qualitative research methods, this study will describe and deeply understand the strategies needed to strengthen the spiritual life of students in the midst of modern challenges and cultural diversity. The results of this study are expected to provide valuable insights and recommendations for Christian schools in developing more effective and relevant spiritual education programs for their students.